2017
DOI: 10.3390/f8120467
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of Close-to-Nature Forests Based on the Combination of Airborne LiDAR Data and Aerial Multispectral Images Using a Single-Tree Approach

Abstract: This study is concerned with the assessment of application possibilities for remote sensing data within a forest inventory in close-to-nature forests. A combination of discrete airborne laser scanning data and multispectral aerial images separately evaluated main tree and forest stand characteristics (i.e., the number of trees, mean height and diameter, tree species, tree height, tree diameter, and tree volume). We used eCognition software (Trimble GeoSpatial, Munich, Germany) for tree species classification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Thus, the applications of ALS in forest studies usually focus on the z dimension -the tree height. Sačkov et al (2017) detected and corrected tree heights using ALS data, and the result showed there was no statistically significant difference compared with the field measured data. Furthermore, in the study of Bouvier et al (2015), it was proved that the heterogeneous canopy structure could be extracted successfully from the ALS data.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the applications of ALS in forest studies usually focus on the z dimension -the tree height. Sačkov et al (2017) detected and corrected tree heights using ALS data, and the result showed there was no statistically significant difference compared with the field measured data. Furthermore, in the study of Bouvier et al (2015), it was proved that the heterogeneous canopy structure could be extracted successfully from the ALS data.…”
Section: Introductionmentioning
confidence: 97%
“…This technology concept has previously been verified in different types of central European forests (e.g. Sačkov et al 2016Sačkov et al , 2017aSačkov et al , 2019. The web-map application was developed as a single page application primarily using Arcgis API libraries for Javascript.…”
mentioning
confidence: 79%
“…Hartling et al [31] demonstrated that deep learning techniques could improve broadleaf species classification by at least 30% compared to RF and SVM. Adding other variables such as LiDAR metrics or topological measures could also improve the classification [8,14,16,22,39,131]. Finally, an expert procedure could be implemented to select a maximum number of each categorical variable to limit over-representation [136].…”
Section: Discussionmentioning
confidence: 99%
“…The first technique generally gives good results, but it is time-consuming, complex and requires advanced LiDAR sensors [17]. The second technique has been studied much more, both at the stand level [18,19] and at the tree level [20][21][22], as there are a variety of algorithms that provide rapid ITC segmentation, which gives satisfactory results [14,16,23].…”
Section: Introductionmentioning
confidence: 99%